Enhancing Doctor-Patient Communication through Digital Media Platforms: A Study on Innovation in Health Interaction - Andi Subhan Amir; Deddy Mulyana; Susanne Dida; Jenny Ratna Suminar (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
In the digital era, communication technology enhances interaction quality across various sectors, including healthcare. Communication between doctors and patients can be improved through innovative digital media platforms. However, there is a knowledge gap regarding the effectiveness and implementation of digital media in doctor-patient interactions. This study aims to evaluate the impact of digital media platforms on doctor-patient communication and identify factors influencing the effectiveness of such communication. This research employs a qualitative method with a case study approach over six months, with inclusion criteria comprising doctors and patients actively using digital media. Subjects were selected through purposive sampling, involving 20 doctors and 50 patients. Data were analyzed using thematic analysis to identify critical patterns and themes. The findings indicate that digital media usage enhances the accessibility and responsiveness of communication, enables real-time health monitoring, and increases patient satisfaction through more personal and interactive communication. Factors such as doctors' digital skills, patients' preferences, and institutional support play significant roles in communication effectiveness. Digital media also reduce communication errors and improve the efficiency of health information delivery. The implications of this study suggest that integrating digital technology in medical communication enhances interaction quality and accelerates digital transformation in the healthcare sector.